2012
DOI: 10.1074/jbc.m111.299115
|View full text |Cite
|
Sign up to set email alerts
|

Lipolysis Response to Endoplasmic Reticulum Stress in Adipose Cells

Abstract: Background: Dysregulation of endoplasmic reticulum homeostasis elicits various stress responses. Results: Endoplasmic reticulum stress activates lipolytic cascade in rat adipocytes. Conclusion:The lipolysis response to endoplasmic reticulum stress is mediated via cAMP/PKA and ERK1/2 signaling. Significance: Increased lipolysis promotes fatty acid efflux from adipocytes to other tissues and thus may contribute to lipotoxicity and insulin resistance in obesity and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 50 publications
5
96
0
1
Order By: Relevance
“…In this context, our data show that incubation with the JNK inhibitor SP600125 (2 h) stimulates the phosphorylation of HSL at Ser 563 and Ser 660 as well as phospho-PKA substrate/perilipin ratio, supporting the idea that JNK inhibition leads to increased lipolysis. However, our current data and previous studies show that the amount of glycerol released into the media is not modifi ed or even reduced by longer-term incubation with SP600125 ( 41,50 ), suggesting that the effects of JNK inhibition on lipolysis might be time dependent. Our results demonstrated that LA induced a time-dependent inhibition of JNK phosphorylation, which might suggest the Supplemental Material can be found at: ( 13,61 ).…”
mentioning
confidence: 41%
“…In this context, our data show that incubation with the JNK inhibitor SP600125 (2 h) stimulates the phosphorylation of HSL at Ser 563 and Ser 660 as well as phospho-PKA substrate/perilipin ratio, supporting the idea that JNK inhibition leads to increased lipolysis. However, our current data and previous studies show that the amount of glycerol released into the media is not modifi ed or even reduced by longer-term incubation with SP600125 ( 41,50 ), suggesting that the effects of JNK inhibition on lipolysis might be time dependent. Our results demonstrated that LA induced a time-dependent inhibition of JNK phosphorylation, which might suggest the Supplemental Material can be found at: ( 13,61 ).…”
mentioning
confidence: 41%
“…as obesity and diabetes, where increased lipolysis occurs in parallel to activation of PKA and HSL phosphorylation at Ser563, Ser660 (31). Based on our observations, HSL and its upstream modulators PKA and MAPK were all suppressed under severe and acute traumatic stress conditions, yet we still observed augmented lipolysis and even more severe …”
Section: Discussionmentioning
confidence: 64%
“…Additionally, ER stress has been shown to induce an intracellular inflammatory cascade and insulin resistance in adipocytes [15] . Our work and other previous studies have shown that ER stress can trigger lipolysis in cultured adipocytes [9,16] . This information suggests that ER stress may be one key pathway leading to metabolic disease states.…”
Section: Introductionmentioning
confidence: 75%
“…The activation of protein kinase A (PKA) and mitogenactivated protein kinase (MAPK) [16] has been shown to be involved in the activation of lipolysis signaling, and we therefore evaluated the activity of these kinases in the tissue samples. As shown in Figure 3D1 and 3D2, the phosphorylation of PKA and MAPK was significantly increased, indicating that these kinases were activated in CKD.…”
Section: Enhanced Lipolysis In White Adipose Tissue In Rrm Ratsmentioning
confidence: 99%